2016
DOI: 10.1002/cncr.30045
|View full text |Cite
|
Sign up to set email alerts
|

Prostate tumor DNA methylation is associated with cigarette smoking and adverse prostate cancer outcomes

Abstract: Background DNA methylation has been hypothesized as a mechanism to explain the association between smoking and adverse prostate cancer (PCa) outcomes. We aimed to assess whether smoking was associated with prostate tumor DNA methylation and whether these alterations may explain, in part, the association of smoking with PCa recurrence and mortality. Methods A total of 523 men had radical prostatectomy as primary treatment, detailed smoking history data, long-term follow-up for PCa outcomes and tumor tissue pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…Each of the conventional prognostic biomarkers (except age) had significant prognostic information on overall survival in this validation cohort (Additional file 1 : Table S23). Differentially methylated genes included three non-melanoma related genes ( MEOX2 , OLIG3 , PON3 ), but previously associated with DNA methylation and cancer prognosis in other pathologies [ 42 44 ]. The DNA methylation levels of the three candidates were validated by pyrosequencing in validation cohort II and survival analyses confirmed their power as indicators of overall and progression-free survival ( P < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Each of the conventional prognostic biomarkers (except age) had significant prognostic information on overall survival in this validation cohort (Additional file 1 : Table S23). Differentially methylated genes included three non-melanoma related genes ( MEOX2 , OLIG3 , PON3 ), but previously associated with DNA methylation and cancer prognosis in other pathologies [ 42 44 ]. The DNA methylation levels of the three candidates were validated by pyrosequencing in validation cohort II and survival analyses confirmed their power as indicators of overall and progression-free survival ( P < 0.05; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, these key genes also played important roles in smoking-related cancers, including lung cancer. Shui et al [29] found the DNA methylation of LGALS3 was associated with smoking status in prostate cancer and strongly correlated with its expression. DNA ligase I (LIG1) is a DNA repair gene involved in both the nucleotide excision repair and the base excision repair pathways [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies in our search still reported significant increases in risk for worse health outcomes when adjusting for clinic-pathologic features [22,24,25,30,32,35,36,38]. Furthermore, recent findings suggest potential mechanisms through which continued smoking can influence tumor progression in this population [40,51].…”
Section: Discussionmentioning
confidence: 81%